Analysis of External Factors Affecting Audit Quality in Indonesia - Wellia Novita; Puspita Rama Nopiana; Yovy Annisa Putri (International Journal of Islamic Business and Management Review, 2022)
This study aims to analyze the effect of audit tenure, auditor reputation and KAP rotation on audit quality, either partially or simultaneously in Indonesian companies, namely manufacturing the basic and chemical industrial sectors listed on the IDX for the 2015-2019 period. The method used is a quantitative method, where the population in the study is to take a total of Indonesian companies, especially manufacturing companies in the basic and chemical industrial sector in Indonesia from the 2015-2019 period, which is as many as 76 companies. Samples taken from the population are those that meet the predetermined criteria, so that only 43 companies are used as samples for this study. The data used for this study were 215 (43 companies x 5 years of financial reporting period). The results of the study explain a) Audit tenure has no significant effect on audit quality, where the audit engagement period is not a problem for quality audits, b) auditor reputation does not significantly affect audit quality in Indonesian companies. This proves that the size of the KAP does not affect the quality of the audit provided, so that the public accounting profession maintains public trust, c) KAP rotation has a significant influence on audit quality in Indonesian companies so that auditors must pay attention to KAP rotation which is regulated by regulations, d) audit tenure, auditor reputation and KAP rotation together have no significant effect on audit quality in Indonesian companies. This is generally regulated by regulations, so it is only necessary to supervise the established procedures so that audit quality can be presented properly and fairly.